ChemInform Abstract: The Direct Synthesis of Hydrogen Peroxide Using Platinum‐Promoted Gold—Palladium Catalysts. Issue 22 (3rd June 2014) - Edwards, Jennifer K.; Pritchard, James; Lu, Li; Piccinini, Marco; Shaw, Greg; Carley, Albert F.; Morgan, David J.; Kiely, Christopher J.; Hutchings, Graham J.
Abstract The addition of a small amount of Pt to a CeO2‐supported AuPd (weight ratio of 1:1) catalyst significantly enhances the activity in the direct synthesis of H2O2 (autoclave, 5% H2/CO2 and 25% O2/CO2, 4.0 MPa, 2 °C, 30 min) and decreases the non‐desired over‐hydrogenation and decomposition reactions.